2018
DOI: 10.3174/ajnr.a5698
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the Stellate and Thoracic Sympathetic Chain Ganglia with High-Resolution 3D-CISS MR Imaging

Abstract: The thoracic sympathetic chain ganglia can be identified on precontrast 3D-CISS MR imaging. This technique may aid in the initial evaluation of stellate ganglion and/or sympathetic chain ganglia size and signal change for comparison in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…Shin et al [ 13 ] found that the mCSG occasionally lies medially to the common carotid artery, distant from the tubercle. Previous studies have suggested that the mCSG may be adjacent to the posterior wall of the carotid sheath [ 12 , 13 ]. All these variations in the mCSG position potentially contribute to the SGB variable efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shin et al [ 13 ] found that the mCSG occasionally lies medially to the common carotid artery, distant from the tubercle. Previous studies have suggested that the mCSG may be adjacent to the posterior wall of the carotid sheath [ 12 , 13 ]. All these variations in the mCSG position potentially contribute to the SGB variable efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [ 11 ] visualized 73 % of the superior CSG using 3T magnetic resonance imaging (MRI). Chaudhry et al [ 12 ] demonstrated that the stellate ganglia could be precisely characterized on pre-contrast three-dimensional constructive interference in steady state MRI. These two ganglia are difficult to detect using HRUS owing to the limited acoustic window, restricted by the bones and lungs.…”
Section: Introductionmentioning
confidence: 99%
“…The CTG/SG can be identified along the sympathetic chain on the border between the neck and thorax, anteriorly and slightly caudad to the head of the first rib11,12, inferior and anterior to the transverse process of C712,19, lateral and posterior to the lateral edge of the longus colli muscle (at the level of T1)11, inferior to the subclavian artery12, medial, posterior, medial and anterior or medial and posterior to the vertebral artery3,11. Which was confirmed also in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…In our study we have tracked down a configuration of the cervico-thoracic ganglia complex not categorized in previous MR study exploring CTG/SG 11,19. The majority of CG-C in our work resembled a question-mark in various configurations: thinner or thicker, mirror, reversed or mirror and upside-down, more or less straight including bludgeon-like shape and an exclamation-mark, or a part of a question-mark: without a dot, resembling kidney or comma.…”
Section: Discussionmentioning
confidence: 99%
“…The sympathetic trunk, extending from the base of the skull to the coccyx, presents bilaterally. It divides into the cervical, thoracic, lumbar and sacral segments [1][2][3].…”
Section: Introductionmentioning
confidence: 99%